Is it important to differentiate between peri-procedural myocardial injury and persistent myocardial scar? - McEntegart, Margaret; Corcoran, David; Berry, Colin (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
With the growth of complex high-risk percutaneous coronary intervention (PCI) it is of increasing importance to be able to quantify procedural risk and describe the consequence of peri-procedural complications. With the increasing prevalence of calcific coronary artery disease (CAD) there is a growing need for adjunctive calcium modifying techniques, with rotational atherectomy (RA) the most commonly used method.